PENGARUH KELELAHAN KERJA DAN KONFLIK PERAN TERHADAP KINERJA KARYAWAN DENGAN STRESS KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan RSUD RA Kartini Jepara) - Wibowo, Bayu Arifianto (Faculty of Economics and Business Diponegoro University, 2015)
The purpose of this research is to analyze the effect of fatigue and role conflict on job stress, job burnout and conflict influence the role of the performance, the effect of work stress on performance. The sample used in this study amounted to 164 (one hundred and sixty-four) employees who are in vulnerable productive and non-productive age. Question is given by using a questionnaire which was distributed through cluster sampling and data analysis methods used is the path analysis using SPSS. In this study formulated five hypotheses, such as: fatigue positive effect on job stress, role conflict positive effect on job stress, job burnout negatively affect performance, role conflict negatively affect performance, work stress negatively affect performance. The results showed that the effect of job burnout, conflict stress the role of the performance of the work as an intervening variable of 72.85%, and 27.15% can be explained by other variables not examined in this study. From the results of the path analysis of job burnout and role conflict and significant positive effect on job stress and job burnout, role conflict and job stress a significant negative effect on the performance of employees.